Optimal design of fractional order PID controller for time-delay systems: an IWLQR technique. Issue 7 (3rd October 2018) - Sumathi, R.; Umasankar, P.
ABSTRACT: In this paper, an optimal design based state feedback gain of fractional order proportional integral derivative (PID) controller for time delay system is proposed. The proposed optimal design is called as IWLQR, which will be the joined execution of both the invasive weed optimization (IWO) and linear quadratic regulator (LQR). The proposed technique modifies a fractional order proportional integral derivative (FOPID) regulator among a high order time delay scheme that achieves an elevated performance for a wide area. In the proposed methodology, the gain of the FOPID controller is tuned to achieve the desired responses which are determined using the LQR theory and the weight matrices of the LQR is anticipated with the assistance of IWO technique. The uniqueness of the projected technique is to reduce the fault in a PID regulator among the higher order time delay scheme by the aid of the increase limits of the regulator. The objective of the proposed control method is chosen in view of the set point parameters and the accomplished parameters from the time delay system. The projected method is employed to achieve the avoidance of high order time delay and the dependability restrictions such as tiny overrun, resolving time and fixed condition defect. This technique is carried out in MATLAB/Simulink platform and the results are separated by the earlier regulator junction representation like Z-N system, Wang technique, curve fitting technique, regression technique which illustrates the superior presentation of the anticipated abstaining in the existing work.